Research on Urban Land Use Change in Ha Noi, Viet Nam Using Remote Sensing and GIS for Planning Oriented Work - Le Thi Minh, Phuong; Vu, Le Anh; Nguyen, Hong Quang (International Journal of Sustainable Construction Engineering and Technology, 2021)
Currently, 55% of the worldâ€™s population lives in urban areas, this proportion is expected to increase to 68% by 2050. In the next 30 years, a large amount of the world’s population is predictably concentrated in urban areas in the developing world. Ha Noi is the capital and largest city of Viet Nam which has the average growth rate of approximately 3% per year. Urban development management has become an important issue in Viet Nam since the negative impacts of the urban sprawl on the environmental sustainability, life quality has been increasing as well. Hence, urban planning and management would be pivotal for creating the effective framework conditions for a sustainable development. The objective of our study is to explore the urban growth of Ha Noi using the Landsat images from 1975 to 2020 compared to the city planning. The volatility analysis information from classified urban land maps is considered supportive for urban management and planning oriented work. In addition, the remote sensing data analysis is a useful tool to support planners, managers for urban management and decision. This study results showed the urban land area in study site city has been growing about 3 times and the largest rate (4-6 times) for the Dong Anh, Tu Liem, Gia Lam and smallest rate (10-25%) for Ba Dinh and Hai Ba Trung districts.